IMPLEMENTASI SYSTEM QUALITY, INFORMATION QUALITY, SERVICE QUALITY TERHADAP PEMBELAJARAN BERBASIS ONLINE DI SAAT PANDEMI COVID-19 (STUDI KASUS PADA MAHASISWA FEB UM METRO) - Suwarto Suwarto; Ardiansyah Japlani; Aninda Amelia (Universitas Muhammadiyah Metro Lampung, 2021)
The problem in this research is in the world of education, in today's world conditions and Indonesia experiencing the COVID-19 epidemic so that the government's appeal stating work from home, social distancing and adjusting the work system does not mean public services and learning are stopped. however, all activities are carried out with the help of information technology or online. This research is an explanatory research, the location of this research is conducted at FEB UM Metro. The sample used is 150. The analytical tool used is SEM where system quality, information quality and service quality have no effect on user satisfaction, but user satisfaction has an effect on net benefits.Keywords: System Quality, Information Quality, Service Quality, User Satisfaction, Net Benefit